Strategi Komunikasi Lingkungan PT Pertamina Hulu Rokan dalam Implementasi TJSL Taman Kehati dan Ekoriparian - Pertiwi, Fadhila Sri; Firdaus, Muhammad; Wirman, Welly (Unitri Press, 2026)
Environmental conservation issues have become a global challenge that demands cross-sector collaboration and active community involvement. Effective environmental communication plays a crucial role in raising awareness, changing behavior, and encouraging public participation in various sustainability initiatives. This study analyzes the environmental communication strategies implemented by PT Pertamina Hulu Rokan (PHR) in its Corporate Social and Environmental Responsibility (TJSL) program, specifically the Biodiversity Park (Taman Kehati) and Ecoriparian initiatives at Lancang Kuning University (Unilak), Riau. A descriptive qualitative method was employed, with data collected through interviews, observations, and documentation, and analyzed using the interactive model of Miles and Huberman. The findings reveal that PHR applies adaptive, participatory, and multi-stakeholder communication strategies, utilizing social media, interpersonal communication, and visual channels to deliver educational and persuasive messages. The evaluation indicates that the program has successfully increased environmental awareness, fostered community participation, and enhanced the educational and recreational functions of the conservation area. However, challenges remain in instilling disciplined waste disposal behavior and expanding public understanding of the area’s long-term goals. Therefore, it is recommended to strengthen digital content, engage local communities as agents of change, and broaden media collaborations. This study contributes to the development of an environmental communication model based on conservation and community empowerment in Indonesia. Abstrak Isu pelestarian lingkungan menjadi tantangan global yang menuntut kolaborasi lintas sektor dan peran aktif masyarakat. Komunikasi lingkungan yang efektif berperan penting dalam membangun kesadaran, mengubah perilaku, dan mendorong partisipasi publik dalam berbagai inisiatif keberlanjutan. Penelitian ini menganalisis strategi komunikasi lingkungan yang diterapkan oleh PT Pertamina Hulu Rokan (PHR) dalam program Tanggung Jawab Sosial dan Lingkungan (TJSL) Taman Keanekaragaman Hayati (Kehati) dan Ekoriparian di Universitas Lancang Kuning (Unilak), Riau. Metode yang digunakan adalah kualitatif deskriptif, dengan pengumpulan data melalui wawancara, observasi, dan dokumentasi, serta analisis data model interaktif Miles dan Huberman. Hasil penelitian menunjukkan bahwa PHR menerapkan strategi komunikasi yang adaptif, partisipatif, dan multi-pihak, dengan media sosial, interpersonal, dan visual sebagai saluran utama penyampaian pesan edukatif dan persuasif. Evaluasi menunjukkan keberhasilan program dalam meningkatkan kesadaran lingkungan, membangun partisipasi komunitas, dan memperkuat fungsi edukatif serta rekreatif kawasan konservasi. Namun, masih terdapat tantangan dalam membentuk budaya membuang sampah yang tertib dan memperluas pemahaman publik mengenai tujuan jangka panjang kawasan. Oleh karena itu, direkomendasikan penguatan konten digital, pelibatan komunitas lokal sebagai agen perubahan, dan perluasan kolaborasi media. Penelitian ini memberikan kontribusi terhadap pengembangan model komunikasi lingkungan berbasis konservasi dan pemberdayaan masyarakat di Indonesia.